Validation of a System xc– Functional Assay in Cultured Astrocytes and Nervous Tissue Samples - Beckers, Pauline; Lara, Olaya; Belo do Nascimento, Ines; Desmet, Nathalie; Massie, Ann; Hermans, Emmanuel (Frontiers in Cellular Neuroscience, 2022)
Disruption of the glutamatergic homeostasis is commonly observed in neurological diseases and has been frequently correlated with the altered expression and/or function of astrocytic high-affinity glutamate transporters. There is, however, a growing interest for the role of the cystine-glutamate exchanger system xc- in controlling glutamate transmission. This exchanger is predominantly expressed in glial cells, especially in microglia and astrocytes, and its dysregulation has been documented in diverse neurological conditions. While most studies have focused on measuring the expression of its specific subunit xCT by RT-qPCR or by Western blotting, the activity of this exchanger in tissue samples remains poorly examined. Indeed, the reported use of sulfur- and carbon-radiolabeled cystine in uptake assays shows several drawbacks related to its short radioactive half-life and its relatively high cost. We here report on the elaborate validation of a method using tritiated glutamate as a substrate for the reversed transport mediated by system xc-. The uptake assay was validated in primary cultured astrocytes, in transfected cells as well as in crude synaptosomes obtained from fresh nervous tissue samples. Working in buffers containing defined concentrations of Na+, allowed us to differentiate the glutamate uptake supported by system xc- or by high-affinity glutamate transporters, as confirmed by using selective pharmacological inhibitors. The specificity was further demonstrated in primary astrocyte cultures from transgenic mice lacking xCT or in cell lines where xCT expression was genetically induced or reduced. As such, this assay appears to be a robust and cost-efficient solution to investigate the activity of this exchanger in physiological and pathological conditions. It also provides a reliable tool for the screening and characterization of new system xc- inhibitors which have been frequently cited as valuable drugs for nervous disorders and cancer.